Materials of the II International Conference “Tumor and Host: Novel Aspects of Old Problem” (November 21–22, 2019, Kyiv, Ukraine) (PH Akademperiodyka, 2023)
INTERACTION OF USP1 PROTEIN AND РН DOMAIN OF BCR PROTEIN AND ITS ROLE IN BCR-ABL EVASION FROM PROTEASOMAL DEGRADATION S.V. Antonenko, G.D. Telegeev Institute of Molecular Biology and Genetics, NAS of Ukraine, Kyiv, Ukraine antonenkoimbg@gmail.com Introduction. Chronic myelogenous leukemia (CML) is characterized by the appearance of the cytogenetic marker of the Philadelphia chromosome (Ph), which is the result of translocation between 9 and 22 chromosomes. The product of this aberration is the hybrid oncoprotein Bcr-Abl.According to the preliminary results of the mass spectrometric analysis, 23 proteins were identified as potential candidates for interaction with the Ph domain of Bcr-Abl oncoprotein. The main function of ubiquitin specific protease 1 (USP1) protein is deubiquitination of cell proteins. As a result of deubiquitination, USP1 protein can prevent proteasomal degradation of Bcr-Abl oncoprotein in a cell and, consequently, contribute to its accumulation and progression of the disease. Aim. To create the pCMVHA-USP1 genetic construct for eukaryotic protein expression and to determine the interaction of USP1 protein with the Рh domain of the Bcr-Abl oncoprotein. Materials and Methods. The amplification of the coding sequence of USP1 gene was performed using primers USP1 fwd AATTGCCTGGTGTCATACCTAGTG and USP1 rev GAGAGACCAATAATATCCAGTAGC, pCMV-XL5-USP1 was used from the plasmid bank of the Department of Molecular Genetics of the IMBG NASU as a template. The resulting sequence of USP1 gene was ligated to pUC18 vector at Sma1 site. USP1 was subcloned to pCMVHA vector using Kpn1 and SalI restriction endonucleases. Co-transfection of pCMVHA-USP1 and pmCitrineC1-PH plasmids into HEK 293T cells was performed using 3:1 ratio of μl PEI : μg DNA. Transfection mixture was added to HEK293T cells and grown for 24 hours at a temperature of +37 °C and 5% CO2. Co-immunoprecipitation of HEK293T cells was done using Sepharose G and anti-His antibodies (Sigma, USA). The results were visualized by Western blot analysis using anti-USP1 antibodies (Thermo Fisher Scientific, USA), anti-His (Sigma, USA). Results and Discussion. Coding sequence of USP1 gene was amplified by PCR and ligated to the pUC18 vector. Genetic construct pCMVHA-USP1 for eukaryotic protein expression was created by sub-cloning the sequence of USP1 gene. Co-transfection of pCMVHA-USP1 and pmCitrineC1-PH vectors in HEK293T cells and co-immunoprecipitation assay revealed the interaction between USP1 protein and Ph domain of the Bcr-Abl oncoprotein. Conclusions. Genetic constructs pUC18-USP1 and pCMVHA-USP1 have been created. For the first time, the interaction between USP1 protein and РН domain of the Bcr-Abl oncoprotein was shown. The results obtained are important for the understanding of signaling in this pathology and may be the basis for the development of new alternative methods of CML treatment. ADSORPTIVE CARBON DRESSING FOR THE TREATMENT OF RAT MODEL WOUND AFTER CISPLATIN ADMINISTRATION AND GUERIN’S CARCINOMA GRAFTING O.Yu. Babchenko, L.A. Sakhno, V.G. Nikolaev R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, NAS of Ukraine, Kyiv, Ukraine helgadoctor@yahoo.com Introduction. The metabolic intoxication and high systemic toxicity of cytostatic therapy affect the dynamics and character of the postoperative wounds healing in cancer patients, and, in particular, in those with purulent-inflammatory complications. In such situations, the use of adsorptive carbon dressing (ACD) that can absorb a number of toxic components from wound content and bind microbial cells seems relevant. Aim. To study the effect of ACD on the healing rate of full-thickness cutaneous wound in rats after cisplatin (CP) administration, and on a complicated wound process in Guerin’s carcinoma-bearing rats after a CP course followed by tumor resection. Materials and Methods. CP was administered to intact inbred rats at a dose of 1 mg/kg bw intravenously every other day (total dose 5 mg/kg). In two days, the animals were inflicted to full-thickness cutaneous wounds of 2.5 cm2 in size in the interscapular region. Gauze dressings were used in control and ACD in experimental group immediately after surgery. The rats were housed in separate cages. In the next group of animals, Guerin’s carcinoma was subcutaneously transplanted into the interscapular region. Three CP injections before and two ones after the surgical intervention for removing the tumor were administered. Closure and state of wounds were assessed via daily planimetry and photo-monitoring. Results and Discussion. The healing terms of wounds in intact rats increased after the course of intravenous administration of СP not less than in 1.3 times (16.7 ± 0.5 vs 22.9 ± 3.0 days). Transient weight loss was observed on the background of CP. After 1–3 bandages in experimental animals, an “artificial black crust” was formed and remained on the wound until it was partially/completely epithelized. The wound surface area in CP-injected rats in 6 and 14 days after the wound infliction was respectively 1.7 and 4.1 times less under ACD than gauze dressings. The healing time for the wounds under ACD was 17.2 ± 1.5 vs 22.0 ± 3.6 days in control. A characteristic difference in the dynamics of the surface area changes of wounds after tumor resection is the absence of an increase in their size for the first three days under ACD, which is inherent for wounds after using gauze dressings. After three days, the average wound surface area in control animals (gauze dressing) was 1.21 times higher as compared with the initial one and vice versa 1.42 times lower under ACD. Visually, within this period, control animals showed swelling of the wound edges and hemorrhages, which were practically absent in experimental ones. Since the fifth day, the wounds in most rats in the experimental group were partially or completely covered with a dry black crust, signs of inflammation were absent. In 7–11 days after the tumor resection, in most rats in both groups tumor growth was resumed under or near the wound. The wounds protected with the crust formed by ACD continued to decrease in size for some time, but the secondary tumor growth lifted or shifted them, interfering the wound healing. The appearance of a wound infection in more than half of the animals in the control group was accompanied by a pronounced unpleasant odor. As a result, the maximum life span was 34 and 63 days, and minimum — 14 and 20 days in control and experimental animals, respectively. Conclusions. Afterintravenous administration of CP in a total dose of 5 mg/kg bw, the healing term of full-thickness cutaneous wounds inflicted to intact rats was 1.3 times longer. The term of healing can be accelerated by applying the ACD. The use of ACD immediately after tumor resection in rats with Guerin’s carcinoma on the background of CP course allows to quickly stop bleeding during surgery and reduce traumatic edema in first days of postoperative period, reduce the risk of local infectious complications in conditions of recurrent growth of carcinoma. The results demonstrate the possibility of ACD use for the prevention and treatment of complicated wounds in cancer patients. DIFFERENT IMMUNOPHENOTYPE OF TAMOXIFEN-RESISTANT AND TAMOXIFEN-SENSITIVE TUMORS N. Babyshkina1, 2, T. Dronova1, 2, S. Patalyak1, E. Slonimskaya1, 3, N. Cherdyntseva1, 2 ¹Cancer Research Institute, Tomsk National Research Medical Center, Tomsk, Russian Federation ²National Research Tomsk State University, Tomsk, Russian Federation 3Siberian State Medical University, Tomsk, Russian Federation nbabyshkina@mail.ru Introduction. Breast cancer stem cells may be involved in tamoxifen resistance by regulating different transduction pathways, including growth factor receptor networks. Aim. To assess the correlation between stem cells markers CD326+CD44+CD24–/low and expression of growth factor receptor factors CD221 (IGF1R) and CD309 (VEGFR2) in breast tumor tissue of patients who developed distant metastasis or recurrence during the adjuvant tamoxifen therapy (a tamoxifen-resistant group) or were responsive to tamoxifen treatment (a tamoxifen-sensitive group). Materials and Methods. Fresh breast tissue specimens were collected from 59 women with hormone receptor-positive primary breast cancer who had received adjuvant tamoxifen treatment at a dose of 20 mg/day for at least 5 years. Multicolor flow cytometry was used to evaluate the expression of CD326+CD44+CD24-/low, CD221, CD309 markers and their co-expression in two patient groups. Results and Discussion. We showed a high expression of CD326+CD221+ as well as CD326+CD309+ markers in tamoxifen-resistant tumors. Co-expression analysis revealed that the population of CD326+CD44+CD24-/low cells were significantly associated with tamoxifen resistance (p = 0.049). The double-positive CD44+CD221+ population was more prevalent in the tamoxifen-resistant patients than in tamoxifen-sensitive group (38.4% vs 21.6%, respectively, p = 0.041). On the contrary, a tamoxifen-sensitive tumors contained the higher percentage of double-negative CD44–CD221– cells compare to tamoxifen-resistant (35.7% vs 14.7%, respectively, p = 0.036). Conclusions. Our preliminary results suggest that the detection of breast cancer stem cells phenotype and their co-expression with growth factor receptor factors could be a useful for the prediction of tamoxifen response. The study was supported by the Russian Scientific Foundation, grant № 19-75-30016. INVESTIGATING THE CORRELATION BETWEEN TRANSFORMING GROWTH FACTOR BETA 1 (TGFβ1) LEVEL AND BLAST CELLS IN PERIPHERAL BLOOD OF ADULTS WITH ACYTE LYMPHOBLASTIC LEUKEMIA V.A. Barilka1, V.L. Matlan2, S.V. Prymak1, O.O. Shalay1, V.E. Logynsky1 1State Institution “Institute of Blood Pathology and Transfusion Medicine of NAMS of Ukraine”, Lviv, Ukraine 2Danylo Halytsky Lviv National Medical University, Ministry of Health of Ukraine, Department of Hematology and Transfusiology, Lviv, Ukraine virabarilka@ukr.net Introduction. The acute lymphoblastic leukemia (ALL) prognosis is unfavorable. Only 30–40% of adults with ALL achieve long-term remission. Therefore, the thorough search for believable prognostic factors in predicting the course of the disease and therapeutic targets is under way. As well known, blood cells together with their leukemic precursors (blasts) in the peripheral blood of ALL patients are affected by environmental cytokines such as TGFβ1. TGFβ1 can be secreted by normal and leukemic cells and activate growth, survival and metastatic pathways of ALL. Aim. To investigate the correlation between TGFβ1 level and blasts in peripheral blood of adults patients with ALL and to set its predictive value. Materials and Methods. Peripheral blood (PB) specimens were obtained from 19 newly-diagnosed adults ALL patients (median age 52 years; range 16–74) and 15 age-matched healthy persons as control group. The diagnosis was based on cytomorphologic and immunophenotypic features of bone marrow aspirates. The concentration of TGFβ1 in plasma and primary culture of PB mononuclear cells (PBMC), which were predominantly presented by blasts, was determined with bioassay cell line CCL64, mink lung epithelial cells. TGFβ1 concentration was estimated in the connection with the blasts count in PB of patients. Results and Discussion. The median of blasts count in PB was 53.0 (range 12–96). TGFβ1 concentration in plasma was 5.21 ± 0.80 ng/ml and exceeded that in healthy persons (2.11 ± 0.38 ng/ml; p < 0.05). TGFβ1 concentration in plasma was not depended on the degree of leukemic infiltration in bone marrow. However, the level of TGFβ1 in plasma had a negative correlation with hemoglobin content (r = –0.27), and counts of lymphocytes (r = –0.26), monocytes (r = –0.36), and platelets (r = –0.91). In patients who did not reach remission and died is several weeks since the diagnosis (n = 7), TGFβ1 concentration was highly correlated with blast count (r = 0.62) that indicated a significant proportion of cytokine production by the leukemic cell clone. Confirmation of such an opinion was given by measuring the concentration of cytokine in PBMC culture (7.36 ± 2.6 ng/ml), which exceeded TGFβ1 plasma level in ALL patients; p <0.001. The correlation coefficient between the TGFβ1 in the primary culture of PBMC and blast count was r = 0.26. TGFβ1 produced by PBMC of the patients with low hemoglobin level (< 100 g/l) was two times higher than that of patients without symptoms of anemia; p < 0.05. Conclusions. Plasma TGFβ1 level was elevated in ALL patients. Increased TGFβ1 concentration in plasma of ALL patients was accompanied by increased blast count in РB and could have a negative influence on normal hematopoiesis with anemia, lymphopenia, thrombocytopenia, and resistance to treatment. The results obtained can testify the use of TGFβ1 assay to assess the course of the disease and point to the probable target for ALL treatment. EPIGENETIC MECHANISMS OF UBIQUITINATION AND SUMOYLATION IN DISORDER OF SPERMATOGENESIS AND INITIATION OF CARCINOGENESIS IN THE TESTIS S.V. Bazalytska, A.M. Romanenko State Institution “Institute of Urology, NAMS of Ukraine”, Kyiv, Ukraine bsvua@i.ua Introduction. Epigenetic regulation is a complex process by which external factors interact with the genome without disrupting the nucleotide DNA sequence, including DNA methylation, effects of microRNA, post-transcriptional modification of histones due to their phosphorylation, acetylation, ubiquitination and sumoylation. Aim. To study the role of the processes of ubiquitination and sumoylation in the regulation of spermatogenesis in male infertility as well as in the initial stages of carcinogenesis, including of patients living in regions of Ukraine contaminated with 137Cs. Materials and Methods. Testicular biopsy specimens of 54 patients with obstructive and non-obstructive secretory forms of male infertility of “clean” and contaminated with 137Cs regions of Ukraine were studied as well as peritumoral tissue of 40 patients with germ cell tumors of the testis using histological and immunohistochemical (IHC) methods for study of the ubiquitin and ubiquitin SUMO proteins. Results and Discussion. A significant increase in the IHC indices of cytoplasmic expression of ubiquitin in Sertoli cells in patients with blocked spermatogenesis and Sertoli cell syndrome was found compared with patients with preserved spermatogenesis (4.8 ± 0.17; 7.4 ± 0.6 and 2.7 ± 0.09, respectively, p ≤ 0.001). In Leydig cells, a significant increase in the cytoplasmic expression of ubiquitin and a simultaneous sharp decrease in its nuclear expression were found. In patients from areas of Ukraine contaminated with 137Cs, the intensification of ubiquitination processes was determined — a significant increase in the cytoplasmic expression of the ubiquitin in Sertoli cells, spermatogenic epithelium and Leydig cells compared to similar observations from “clean” regions. IHC expression of the ubiquitin SUMO correlated with certain patterns of the ubiquitin protein expression with overall low IHC indices. It was found that in peritumoral testicular tissue in the seminiferous tubules with blocked spermatogenesis, which constitute 95% of observations, in spermatogonia, spermatocytes and spermatids, as well as in Sertoli cells, ubiquitination process significantly increased (3.5–4-fold increase of IHC coefficient as compared with observations from “clean” regions and 2.5–3-fold increase as compared with observations from radiocontaminated regions), which indicates an intense process of proteolysis and post-translation modification of intracellular proteins. Conclusions. The established patterns indicate the involvement of the epigenetic mechanisms of ubiquitination and sumoylation in the regulation of spermatogenesis and the participation of components of the ubiquitin-proteolysis system in the initiation of carcinogenesis, which can be induced by persistent long-term low doses of ionizing radiation in humans. CONTENT OF CANCER STEM CELLS AND IMMUNOCOMPETENT CELLS IN GLIOMA INFILTRATION L.M. Belska State Institution “Romodanov Neurosurgery Institute, NAMS of Ukraine”, Kyiv, Ukraine nimun.neuro@ gmail.com Introduction. The role of stem and intratumoral immunocompetent cells in the development and progression of tumor is in the focus of current studies. Infiltration of central nervous system tumors with CD133+ cancer stem cells (CSC), macrophages/microglia, neutrophils, T-regulatory cells, etc. was shown. At the same time, many questions regarding their role in tumorogenesis remain unexplored, indicating the need for further research. Aim. To investigate the level of infiltration of glial tumors of various degrees with CSC and immunocompetent cells. Materials and Methods. 32 samples of glioma of varying degrees of malignancy were obtained from patients during neurosurgical operations. The phenotype of the cells was studied using monoclonal antibodies to CD3, CD4, CD8, CD16, CD133 molecules under the flow cytometry protocol (FACS Calibur “FC-500”, Beckman Coulter, USA) according to the Cytomics CXP Softwar program in accordance with the guidelines. Results and Discussion. In glioma biopsies with high level CD 133+ CSC the number of cells with CD4+ phenotype was increased by 1.4 times and the number of CD8+ cells was reduced by 1.7 times compared to the gliomas with low content of CD 133+ CSC. There was no statistically significant difference between the relative content of CD16+ NK cells in glioma biopsies depending on the content of CD133+ CSC, however, in 43.5% of the samples, the level of NK cells was 1,3 times lower in biopsy samples with high content of CD133+ CSC. In our opinion, this decrease in the number of effector cells (NK and cytotoxic T lymphocytes) may be due to TGF-β1 production by CSC, which results in inhibition of the expression of NKG2 CD8+ T and NK cells. It is impossible to exclude the indirect effect of CSC through T-reg cells on the proliferative potential of effector cells, since the production of CSC chemokine CCCL2 receptor for T-reg cells is described, which promotes the homing of T reg cells (CD4+CD25+) into glioma tissue. In our opinion, this assumption is confirmed by the increase in the content of cells with CD4+ phenotype in biopsy samples of glioma with high content of CD133+ CSC. Conclusions. The level of cytotoxic immune cells in the tumor foci depends on the CSC content in the tumor tissue indicating the selective immunosuppressive properties of CSC. MESENCHYMAL STEM CELL: REGULATION OF INNATE IMMUNITY CELLS N.M. Berezhnaya R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, NAS of Ukraine, Kyiv, Ukraine In 1978, Friedenstein et al. were the first who discovered in human bone marrow the cells that were previously unknown. These were adhesive non-hematopoietic fibroblast-like cells (“precursors of stromal mechanocytes”) that possess clonogenicity and high proliferative potential and can differentiate into various connective tissue lineages (osteoblasts, adipocytes, chondrocytes, myocytes and neurons). Later on, these cells were identified as mesenchymal stem cells (MSC) (A. Caplan) and such definition became generally accepted. Subsequently, MSC was a subject of thorough studies and copious information was accumulated on MSC role in adaptive immunity. Nevertheless, the role of MSC in functions of the innate immunity cells has been underestimated for a long time. Only recently, the novel data appeared shedding some light onto the regulatory function of MSC on such cells as neutrophils, macrophages, monocytes, microglia, and innate lymphoid cells. The effects of MSC on these cells are manifold and depend on biological features of these cells as well as their localization. For neutrophis, the predominant effects mediated by MSC are regulation of the recognition of non-self antigens, involvement in the inflammatory process, protection from apoptotic death (without phagocytosis and cytotoxicity). Unlike neutrophils, for the cells of microglia, the preponderant effects are manifested as modulation of immunologic phenotype in the brain and the induction of neurogenesis. Analyzing the available data on the MSC effects on the phagocyting cells, the following may be noted: i) Interaction between MSC with each type of phagocyting cells is different; ii) The peculiar features of such interactions depend mostly on their localization; iii) there has been increasingly recognized that the permanent activation of neutrophils may facilitate the induction of the malignant transformation, especially in the setting of the chronic inflammatory conditions. The possibility of inducing the malignant growth in the association with neutrophil activation was demonstrated by H. Dvorak in 1970s of the past century. Such possibility was later confirmed by V.G. Pinchuk in Ukraine in ultrastructure studies. The repost will disclose the particular features of the interactions of MCS with rather different types of phagocytic cells (both by their origin and by biological properties) such as neutrophils and cells of microglia. Unfortunately, the data on the role of phagocyting cells in the induction of the malignant growth is highly limited. Nevertheless, there are good grounds for further developments and expansion in this area that may be challenging for better understanding of the pathogenesis of cancer. BRONCHOSCOPIC AND CYTOLOGICAL STUDIES IN THE CENTRAL GROWTH OF LUNG CANCER L.S. Bolgova1, T.M. Tuganova1, O.I. Alekseenko1, A.O. Ponomarenko2 1National Cancer Institute, Ministry of Health of Ukraine, Kyiv, Ukraine 2National University “Kyiv-Mohyla Academy”, Kyiv, Ukraine bolgova2006@ukr.net Introduction. Lung cancer (LC) is still the most common neoplasm in men and has become more frequent in women in economically developed countries. According to the Bulletin of the National Cancer Register № 19 (2018), the incidence of LC in Ukraine is 60.3 in men and 13.5 cases in women per 100 thousand of population. Therefore, the study of diagnostics and histogenesis of LC remains relevant and important for improving the diagnosis the effectiveness of treatment. Aim. The purpose of our work is to examine the dependence of the growth of central LC relative to the mucous membrane of the bronchi. Materials and Methods. The cytological method and the method of bronchoscopy. Results and Discussion. Fibrobronchoscopy and cytological examination of the specimens were performed in 14 patients with central LC who were surveyed and treated at the National Cancer Institute. According to bronchoscopic data, exophytic growth, compression of the thickened bronchus outside or the spread of tumor damaging 2–3 bronchi have been revealed. Depending on the spread of the tumor, the lungs of the patients under study were divided into 3 groups. The first group included 4 (28.6%) patients, in whom the tumor spread by more than 2–3 bronchi. In 3 (75%) of these 4 patients, penetration of the bronchial mucosa was noted, and in the bronchial scrapes the elements of cancer were noted. In the second group narrowing of 1–2 bronchi due to compression from the outside was observed in 5 (35.7%) patients. In four (80%) of these 5 patients, penetration of the tumor was observed in relation to the cylindrical epithelium. In the third group, only exophytic tumor growth was seen in 5 (35.7%) patients, and only in one patient of this group cancer cells were found in the scrapes examined from the surface of the tumor. Thus, a fibrobronchoscopic examination and a cytological study of scrapes from the exophytic part of LC made it possible to state that in 8 (57.1%) patients cancer cells were found, indicating the penetration of the bronchial mucosal tumor. In 6 (42.9%) patients in the exophytic tumor scrapes only the cells of the cylindrical epithelium were found, that is, the tumor grew out of the bronchial mucosa. Conclusions. The obtained results indicate that central LC may develop from the peribronchial part, namely from cells of type II pneumocytes that are branched in peribronchial glands. GENOME INSTABILITY AND ENDOCRINE-METABOLIC HOMEOSTASIS IN ENDOMETRIAL CANCER PATIENTS O.V. Brieieva1, S.V. Nespryadko2, L.G. Buchynska1 1R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, NAS of Ukraine, Kyiv, Ukraine 2National Cancer Institute, Ministry of Health of Ukraine, Kyiv, Ukraine olha.brie@gmail.com Introduction. The genotoxic influence of estrogen metabolites, especially 4-hydroxyestradiol (4OHE2), is considered as one of the key factors of hormonal carcinogenesis. It is believed that hormonal imbalance, metabolic disorders and inherited sensitivity to the genotoxic agents may have a significant impact on endometrial cancer (EC) pathogenesis. In this regard, studies on the relationship between endocrine and metabolic changes, family history features and genome instability in peripheral blood lymphocytes (PBLs) and tumor cells of EC patients are needed. Aim. To assess DNA damage level and DNA repair efficiency in PBLs and tumor cells of EC patients in relation to the presence of obesity, menstrual function and a family history of cancer. Materials and Methods. 106 EC patients were included in the study. DNA damage level in PBLs and tumor cells was evaluated by comet assay and expressed as the percentage of DNA in the comet tails (% tail DNA). DNA repair efficiency was determined by calculating the ratio between repaired and induced DNA damage after incubation of PBLs with bleomycin or 4OHE2 (%). Body mass index values of < 30 kg/m2 were considered as normal weight and ≥ 30 kg/m2 as obese. Results and Discussion. It was revealed that in PBLs of obese EC patients, the level of baseline DNA damage was significantly higher than in women with normal weight (8.1 ± 0.9 and 5.0 ± 0.7% tail DNA, respectively, p < 0.05). A similar tendency was found for tumor cells of EC patients (28.2 ± 2.1 and 20.4 ± 2.4% tail DNA, respectively, p < 0.05). In addition, a significantly higher level of baseline DNA damage was detected in tumor cells of menopausal patients (27.3 ± 1.7% tail DNA) compared to women with regular menstrual cycles (15.5 ± 3.2% tail DNA) (p < 0.05). After incubation with bleomycin, the level of DNA damage in the PBLs increased to 96.6 ± 0.7% tail DNA, and the influence of 4OHE2 led to its rising to 39.9 ± 2.0% tail DNA. When analyzing the repair processes, lower DNA repair efficiency of bleomycin-induced damage was detected in menopausal women (44.9 ± 4.7%) than in patients with regular menstrual cycles (61.2 ± 3.7%) (p < 0.05). Furthermore, in PBLs of obese EC patients with a family history of cancer, reduced DNA repair efficiency of 4OHE2-induced damage versus patients with normal weight was observed (15.0 ± 8.8 and 31.2 ± 11.7%, respectively). Conclusions. PBLs and tumor cells of obese and menopausal EC patients are characterized by an increased level of baseline DNA damage along with decreased DNA repair efficiency that may be modulated by a family history of cancer. The data obtained indicate the significant role of endocrine and metabolic changes in determining the level of genome instability in cells of EC patients. ANAEMIA IN GASTRIC CANCER PATIENTS WITH OVERWEIGHT: ASSOCIATION WITH INTRATUMORAL CANCER-ASSOCIATED ADIPOCYTES, HYPOXIA AND ANGIOGENESIS L. Bubnovskaya1, S. Merentsev2, I. Ganusevich1, D. Osinsky2 1R.E. Kavetsky Institute of Experimental Pathology, Oncologyand Radiobiology, NAS of Ukraine, Kyiv, Ukraine 2City Clinical Oncological Center, Kyiv, Ukraine osinskysp12@ukr.net Introduction. Anemia prevalence and incidence in cancer patients are high. Cancer-induced anemia has been identified as an adverse prognostic factor due to a link between preoperative hemoglobin level and tumor oxygenation as well as angiogenesis. The presence of anemia might reflect more aggressive tumor phenotype. Excess body weight and weight gain have been reported to increase independently the risk of several cancers. In the setting of overweigh and obesity, microenvironment of tumor with high density of cancer-associated adipocytes (CAA) plays a special role in tumor progression. Understanding the causal association by which anemia and obesity drive cancer progression is essential for the development of novel precision therapy for obese cancer patients. Aim. To evaluate the relationship between anemia and high density of САА in tumor microenvironment in the setting of overweight. Materials and Methods. A total of 125 patients (59 men and 66 women) with primary gastric cancer (GC) were enrolled into the study. No patients received chemotherapy or radiation prior to surgery. All patients were thoroughly informed about the study that was approved by the Local Ethics Committee. Anemia was defined as Hgb < 13 g/dL in males and Hgb < 12 g/dL in females. Hypoxia level was evaluated by 31NMR spectroscopy: if the phosphomonoester/inorganic phosphate (PME/Pi) ratio < 1.4, tumors were characterized as hypoxic, whilst if PME/Pi > 1.4, the state of weak hypoxia was stated. Tumor adipocytes have been calculated as Plin5+-cells that were detected by immunostaining as well expressions of VEGF, CD34 and MVD, assessed by the hot spot method. The body mass index (BMI) was calculated as weight (kg)/height2 (m2). Results and Discussion. Preoperative anemia was detected in 54.3% patients with prevalence of moderate anemia. 36.6%, 48.4% and 86.4% of high CAA was determined in tumors of patients with BMI < 25 kg/m2, BMI 25–30 kg/m2 and BMI > 30 kg/m2, respectively. Probability of high density of САА (> median) in tumors of grade 1 obesity is increased by a factor of 8.84 (χ2 = 13.47, 95% CI 4.665–16.777, р < 0.001) as compared with patients with BMI < 30. In nonanemic patients, level of hypoxia is not associated with BMI. In anemic patients with BMI < 25 kg/m2, tumors were weakly hypoxic PME/Pi > 1.59 (satisfactory oxygenated). In BMI 25–30 kg/m2 tumors were more hypoxic (PME/Pi > 1.36), and in patients with grade 1 obesity (30–35 kg/m2), tumors were much more hypoxic (PME/Pi > 1.27). In anemic patients with BMI > 30 kg/m2, a probability that tumors are hypoxic increased by a factor of 7.13 (odds ratio 7.13, χ2 = 3.95, 95% CI 3.57–14.225, p < 0.05). The association between high density of CAA (> median) and high expression of VEGF in tumor was found: in 82.4% anaemic patients of grade 1 obesity with high CAA density, probability of high VEGF expression (> median) in tumor increased by a factor of 4.01 (OR 4.01, χ2 = 6.43, 95% CI 1.339–6.867, p < 0.05) as compared with patients with BMI < 30. Moreover, tumors of these patients were characterized by hypovascularization. In nonanemic patients, tumor vascularization was not dependent on BMI. Conclusions. It was shown that preoperative anemia of patients with overweight and especially grade 1 obesity is associated with high САА density that enhances tumor aggressiveness. It may be relevant to take into account pretreatment anemia in therapeutic concept for cancer treatment in such groups of patients. ANAEMIA IN GASTRIC CANCER PATIENTS: ASSOCIATION WITH INTRATUMORAL HYPOXIA AND ANGIOGENESIS L. Bubnovskaya1, S. Merentsev2, I. Ganusevich1, D. Osinsky2 1R.E. Kavetsky Institute of Experimental Pathology, Oncologyand Radiobiology, NAS of Ukraine, Kyiv, Ukraine 2City Clinical Oncological Center, Kyiv, Ukraine osinskysp12@ukr.net Introduction. The treatment outcome of gastric cancer (GC) is still not satisfactory because of objective difficulties in diagnosis and prediction of tumor response to treatment as well as prognosis of disease outcome. Anemia has come to be viewed as a relatively common condition in patients with cancer with the actual incidence largely dependent on the type and extent of the malignancy and has also been identified as an adverse prognostic factor. It has been hypothesized that the presence of anemia might reflect a more aggressive tumor phenotype. Such factors as hemoglobin level, an expression of vascular endothelial growth factor (VEGF), microvessel density (MVD) reflect tumor oxygenation. A causative relationship between anemia — tumor hypoxia — tumor aggressiveness mediated by angiogenesis up-regulation is advocated but yet remains controversial. Aim. To analyze the relationship between anemia, tumor hypoxia, and angiogenesis of GC patients. Materials and Methods. A total of 112 patients (64 men and 48 women) with primary GC were enrolled into the study. No patients received chemotherapy or radiation prior to surgery. All patients were thoroughly informed about the study that was approved by the Local Ethics Committee. Anemia was defined as Hgb < 13 g/dL in males and Hgb < 12 g/dL in females. Hypoxia level was evaluated by 31NMR spectroscopy: if the phosphomonoester/inorganic phosphate (PME/Pi) ratio < 1.4, tumors were characterized as hypoxic, whilst if PME/Pi > 1.4, the weak hypoxia was stated. Expressions of VEGF, HIF-1 alpha, CD34 were detected by immunostaining and MVD, assessed by the hot spot method. Results and Discussion. Preoperative anemia was detected in 48.7% patients with prevalence of moderate anemia: 10.9 g/dL (6.7–11.4 g/dL) — 45.4% and 9.5 g/dL (7.8–11.8 g/dL) — 54.5% in males and females patients, respectively. It was found that in anemic patients a probability that tumors are hypoxic increased by a factor of 3.0 (odds ratio 3.23, χ2 = 7.42, 95% CI 1.13–4.70, p < 0.01) and even more in female patients when anemia was less than 9.0 g/dL (odds ratio 4.48, χ2 = 5.99, 95% CI 2.270–9.97, p < 0.05) as compared to nonanemic patients; positive expression of VEGF was detected in 71.4% of cases with high number of VEGF-positive cells (> median, odds ratio 2.52, p > 0.05). There was a trend towards low level of MVD (< median, odds ratio 2.97, χ2 = 7.88, 95% CI 2.04–4.323, p < 0.01) in tumors of patients with pretreatment anemia being a sign of more depth of invasion. There was no significant correlation between MVD and hypoxia level, as well with VEGF expression, but direct correlation between hypoxia level and VEGF expression in tumor tissue (p = 0.027) was found. We failed to show the differences in HIF-1 alpha expression in tumors of anemic and nonanemic patients. Conclusions. It was detected that pre-operative anemiaincidence in GC patients are high. The results obtained have clearly shown that anemia relates to tumor aggressiveness due to a link between preoperative hemoglobin level and tumor oxygenation, as well as with high level of VEGF expression and low tumor vascularization that characterize more aggressive tumors. Therefore preoperative anemia may be a sign of a destructive impact of a tumor on its host and an increased risk of failure independent of the treatment modality and may help to pave the way for more effective treatments. ROLE OF THE COMPONENTS OF TUMOR MICROENVIRONMENT IN MODULATING PROGRESSION AND COURSE OF THE DISEASE IN PATIENTS WITH ENDOMETRIAL CANCER AND AGGREGATION OF ONCOPATHOLOGY IN FAMILIES L.G. Buchynska, N.P. Iurchenko R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, NAS of Ukraine, Kyiv, Ukraine laboncogen@gmail.сom Introduction. Endometrial cancer (EC) is a multifactorial pathology with a significant contribution of the hereditary component and is heterogeneous in terms of phenotypic characteristics, both of tumor cells and microenvironment components. The presented features of malignant neoplasms, along with the components of tumor microenvironment underlie such indices of tumor progression as growth rate, angiogenic, invasive and metastatic potential, determining the variability of the clinical course of the disease. Therefore, the study of association of phenotypic features of tumors, their microenvironment and clinical and pathological characteristics of patients with EC accounting their genealogical status, remains the priority in terms of assessing the aggressiveness of the neoplastic process. Aim. To identify the phenotype of tumor cells in EC patients with family history of cancer and evaluate its association with clinical course of the disease. Materials and Methods. The study was performed on the samples of surgical material of 170 patients with EC of stages I–II (mean age 57.3 ± 0.8 years), using morphological, immunohistochemical and statistical methods. Results and Discussion. It was found that in 20.5% of pedigrees of patients with EC there is an accumulation of malignant tumors of different genesis with a predominance (73.3%) of cancer of the organs of the female reproductive system and the gastrointestinal tract. In patients with EC with a family history of cancer, a significantly higher expression of tumor-suppressor proteins FOXP3 and р16INK4a, and a decreased expression of p53 and Ki-67 were observed, while the content of FOXP3+-intratumoral lymphocytes decreased in comparison with these indices in endometrial carcinomas of patients without aggregation of tumor pathology in pedigrees. A progressive increase in the expression of Ki-67 and p53 proteins in parallel with a decrease in the EC differentiation grade in both groups of patients was shown. It should be noted that the changes in the expression of inhibitors of two families of cyclin-dependent kinases р16INK4a and р21WAF1/CIP1 in tumors of patients depending on the burden of a family history of cancer were oppositely directed. In the endometrial carcinomas of the EC patients with a family history of cancer, an increase in expression of р16INK4a (by 20.3 ± 3.2%) and a decrease of p21WAF1/CIP1 (by 9.2 ± 3.0%) in G3 tumors was observed in comparison with G1 (by 12.4 ± 1.3% and 18.1 ± 2.2% respectively). For the first time, it was found that 5-year survival rate of the EC patients with family history of cancer is significantly higher (92.0%) compared with that of patients without aggregation of oncological pathology in pedigrees (73.0%, p < 0.05). It has been determined that the most informative prognostic markers of the favorable course of the disease in patients with a family history of cancer are low (< Me) content of intratumoral FOXP3+ lymphocytes and low (< Me) expression of the proliferation marker Ki-67. Conclusions. On the basis of a complex clinical-morphological, genetic and molecular research, it was established that the biological polymorphism of EC of stages I–II is related to the genealogical status of patients with oncological pathology, the molecular tumor phenotype and factors of tumor microenvironment, which determines the degree of tumor malignancy and the course of the disease. NO ASSOCIATION BETWEEN RS1899663 HOTAIR SINGLE NUCLEOTIDE POLYMORPHISM AND PROSTATE ADENOCARCINOMA METASTASIS IN UKRAINIAN POPULATION Ya.D. Chumachenko1, A.D. Volkohon2 1Scientific Laboratory of Molecular Genetic Research of Sumy State University, Sumy, Ukraine 2Department of Surgery and Oncology, Sumy State University, Sumy, Ukraine yaroslavus.dm@gmail.com, volkohon@ukr.net Introduction. Non-coding RNAs (ncRNAs) implement a number of important cellular processes such as differentiation, proliferation, X-chromosome inactivation and imprinting. HOX transcript antisense RNA (HOTAIR) belongs to long ncRNAs and realizes epigenetic regulation of different genes expression. In physiological conditions it serves as a scaffold for lysine specific demethylase 1 (LSD1) and Polycomb repressive complex 2 (PRC2) that suppress HOXD gene cluster activity through Lysine (Lys) 4 demethylation and Lys27 trimethylation of histone H3 respectively. But current studies show that HOTAIR could activate androgen receptor and thus enhances proliferative and invasion properties of prostate adenocarcinoma (PA) cells. Moreover, it was found that G to T transversion (rs1899663) in HOTAIR gene changes the affinity of this lncRNA to various transcription factors related to progression and recurrence of different tumors, including PA. Aim. To analyze the association between rs1899663 HOTAIR single nucleotide polymorphism (SNP) and PA metastasis in Ukrainian population. Materials and Methods. Venous blood of 184 patients with diagnosed PA (80 subjects with metastatic foci and 104 individuals without metastasis) was collected for DNA extraction. Polymerase chain reaction-restriction fragment length polymorphism was used for rs1899663 HOTAIR genotyping. All statistical calculations were performed using Statistical Package for Social Science software (version 17.0, Chicago, IL, USA) and p < 0.05 was accepted as significant. Results and Discussion. The following distribution of genotypes among PA patients with and without metastasis, respectively, was found: GG — 33.7%, GT — 53.8%, TT — 12.5%, and GG — 45.2%, GT — 44.2%, TT — 10.6%. But according to the χ2-test there was no significant differences in genotype frequencies (p = 0.291). Logistic regression analysis showed the lack of association between rs1899663 HOTAIR and PA metastasis neither in crude dominant, recessive, additive and over-dominant models of inheritance nor after the adjustment for age, smoking and drinking (p > 0.05). Nowadays a small amount of studies is devoted to the investigation of the association between rs1899663 HOTAIR and PA development. Taheri et al. showed the over-presentation of T-allele and TT-genotype among patients with PA compared to subjects with benign prostate hyperplasia. Thus, further population studies are necessary for the correct estimation of rs1899663 HOTAIR SNP and PA development. Conclusions. There is no association between rs1899663 HOTAIR SNP and PA metastasis in Ukrainian population. CHARACTERISTICS OF BREAST CANCER PROGRESSION Yu.Ya. Chuprovska, A.S. Kondratova Higher State Educational Institution of Ukraine “Bukovyna State Medical University”, Chernivtsi, Ukraine chuprovska.julia@gmail.com Introduction. Despite the rapid development of oncology, the prediction of breast cancer metastasis still remains a disputable and unexplored issue. A retrospective study of the characteristics of breast cancer progression will provide an opportunity to better understanding of the problem. This one can serve as the basis for further research aimed at identifying objective criteria for predicting breast cancer progression. Aim. To study the clinical and statistical characteristics of the breast cancer course with the verified progression of the tumor process, depending on the stage of the disease and the molecular subtype of the tumor. Materials and Methods. A retrospective analysis of 242 outpatient records of patients with breast cancer was carried out. The female patients, depending on the breast cancer progression after treatment, were divided into two groups: the first group consisted of 179 people “without breast cancer progression” and the second one — 63 (26.0%) people “with verified breast cancer progression”. The median age of the patients was 57.3 ± 0.69 years. Results and Discussion. On the basis of the data obtained, it can be concluded that there is a clear dependency between the increase in the percentage of the patients with breast cancer progression and the stage of the disease. There is no significant difference as to the rate of progression between the two research groups accounting for median age, the frequency of the right or left mammary glands lesions, or the number of regional lymph nodes affected by metastases. The only distinctive feature was that in group with breast cancer progression, the percentage of patients with larger tumor size was higher. The longest period to verify the progression of breast cancer is common for stage II B of the disease, with the Luminal-A subtype of the tumor. Conclusions. All of the listed: age, localization of tumors in the right or left breast, and the number of regional lymph nodes affected by metastases do not affect the breast cancer progression. Within, larger average tumor size is noted, especially with the Luminal-A subtype of the tumor. The longest period to verify the progression of breast cancer is common for stage II B of the disease, with the Luminal-A subtype. ANTICANCER EFFECTIVENESS OF XENOVACCINES IN MOUSE TUMOR MODEL A. Darinskas1, 2, J.A. Krasko1, 2, K. Žinioytė1, 3, V. Pašukonienė1 1Laboratory of Immunology, National Cancer Institute, Vilnius, Lithuania 2JSC Froceth, Vilnius, Lithuania 3Vilnius University, Vilnius, Lithuania vita.pasukoniene@nvi.lt Introduction. Immunotherapy in the form of anticancer vaccination relies on the mobilization of the patient’s immune system against specific cancer antigens. Instead of focusing on an autologous cell lysate, which is not always available in clinical practice, the present study investigates vaccines utilizing xenogeneic fetal tissues that are rich in oncofetal antigens and compares them with autologous vaccines. Lewis lung carcinoma and melanoma (B16)-challenged C57BL/6 mice were treated with xenogeneic vaccines made from chicken whole embryo, rat brain tissue, different sheep fetal organ antigens, supplemented with organic and synthetic adjuvants (Bacillus subtilis protein fraction, bacterial ghosts, azoximer bromide, meglumine acridone acetate, polyA-polyU). Aim. To evaluate and compare the antitumour effectiveness of autologous and xenogenic vaccines in vivo in mouse melanoma and lung carcinoma models. Materials and Methods. Follow-up of survival of tumor-bearing mice after vaccination with all different types of vaccines, evaluation of tumor growth and spread of metastasis, phenotyping of peripheral blood lymphocytes, histological evaluation of lung tissue. Results and Conclusions. Xenogeneic vaccination can have a significant impact on survival of mice challenged with metastatic and non-metastatic cancer. Xenogeneic vaccines achieve higher survival benefit in mice than autologous lysate-based vaccination in metastatic cancer setting. Some xenogeneic vaccines require adjuvanation to achieve positive clinical outcome to increase the phagocytic capabilities of antigen presenting cells (PolyX adjuvant), whereas autologous lysate-based vaccines require adjuvanation to mitigate the immunosuppressive properties of tumor lysate (BGs platform). Adjuvanted autologous lysate-based vaccines and xenogeneic vaccines cause an increase in CD8+ lymphocyte count and contribute to smaller metastatic spread. CD8+ cell count strongly correlates with survival rate in mice vaccinated with autologous lysate-based vaccines or xenogeneic vaccines. IMPACT OF RECEPTOR EPIDERMAL GROWTH FACTOR ON THE ENDOCRINE RESISTANCE IN LUMINAL BREAST CANCER PATIENTS T.A. Dronova1, 2, N.N. Babyshkina1, 2, M.V. Zavyalova1-3, E.M. Slonimskaya1, 3, N.V. Cherdyntseva1, 2 ¹Cancer Research Institute, Tomsk National Research Medical Center, Tomsk, Russian Federation ²National Research Tomsk State University, Tomsk, Russian Federation 3Siberian State Medical University, Tomsk, Russian Federation tanyadronova@mail.ru Introduction. It is well documented that the bidirectional cross-talk between estrogen receptor alpha (ERα) and growth factor receptor pathways plays an important role in the development of endocrine resistance. Aim. To examine the relationship between mRNA level, protein expression and gene polymorphism of the epidermal growth factor receptor (EGFR) and ERα with endocrine therapy efficacy and prognosis in patients with luminal breast cancer. Materials and Methods. The study included 141 breast cancer patients who had received adjuvant endocrine treatment (tamoxifen or aromatase inhibitors), of which 31 patients developed recurrence or distant metastasis after endocrine therapy (hormone resistance group), 110 patients did not develop any disease progression (hormone sensitive group). The EGFR (rs2227983, rs1468727) and ERS1 (rs2228480, rs2077647, rs1801132, rs3798577) SNPs were detected by a TaqMan assay. The relative expression of mRNA for EGFR and ESR1 was analyzed using RT-PCR analysis. EGFR protein expression level of was assessed by immunohistochemistry. Progression-free survival was evaluated using Kaplan — Meier analysis. Results and Discussion. The mutant genotypes of ESR1 at both locus rs2228480 and rs3798577 were more frequent among hormone resistance group patients compared with to hormone sensitive group (p = 0.040 and p = 0.007; respectively). We identified a low ERS1 mRNA expression level in patients who developed distant metastasis or recurrence after endocrine in contrast to the distant metastasi